Liposome-polyethylenimine complexes for the effective delivery of HuR siRNA in the treatment of diabetic retinopathy - Supe, Shibani; Upadhya, Archana; Tripathi, Santosh; Dighe, Vikas; Singh, Kavita (Drug delivery and translational research, 2023)
Diabetic retinopathy (DR) is a vision-impairing complication of diabetes, damaging the retinal microcirculatory system. Overexpression of VEGF (vascular endothelial growth factor) is implicated in the pathogenesis of DR. Human antigen R (HuR) is an RNA-binding protein that favorably regulates VEGF protein expression by binding to VEGF-encoding mRNA. Downregulating HuR via RNA interference strategies using small interfering RNAs (siRNAs) may constitute a novel therapeutic method for preventing VEGF protein overexpression in DR. Delivery of siRNAs to the cellular cytoplasm can be facilitated by cationic peptides or polymers and lipids. In this study, a cationic polymer (polyethylenimine (PEI)) and lipid nanoparticles (liposomes) were co-formulated with siRNA to form lipopolyplexes (LPPs) for the delivery of HuR siRNA. LPPs-siRNA were analyzed for size, zeta potential, serum stability, RNase stability, heparin stability, toxicity, and siRNA encapsulation efficiency. Cellular uptake, downregulation of the target HuR (mRNA and protein), and associated VEGF protein were used to demonstrate the biological efficacy of the LPPs-HuR siRNA, in vitro (human ARPE-19 cells), and in vivo (Wistar rats). In vivo efficacy study was performed by injecting LPPs-HuR siRNA formulations into the eye of streptozotocin (STZ)–induced diabetic rats after the development of retinopathy. Our findings demonstrated that high retinal HuR and VEGF levels observed in the eyes of untreated STZ rats were lowered after LPPs-HuR siRNA administration. Our observations indicate that intravitreal treatment with HuR siRNA is a promising option for DR using LPPs as delivery agents. Graphical Abstract